A Vocal Recital by Malliga Chompoo - choompoo, malliga; Premananda , Weerachat (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2021)
A master vocal recital by Malliga Chompoo in specific purposefor presenting a interpretation and emotions expression of one and second sets Old American Songs, which was compiled by the legendary American composer of Aaron Copland, since AD.,1950 and 1952. In 10th arts of singing was poems that convey the various charms of American’s culture, in the research section, also, consists of analysis and design methods of conveying the lyrics to the tender text of song parable by designed using advanced skills, including the importance of designing and creating display plans, training, recording management for professional quality, dissemination of master vocal recital by Malliga Chompoo can be viewed on YouTube in the show series on June 15, 2020 under “Malliga Chompoo’s Master Vocal Recital”